PARTISIPASI MASYARAKAT DALAM MUSYAWARAH PERENCANAAN PEMBANGUNAN DESA (Studi Kasus di Desa Jambai Makmur Kecamatan Kandis Kabupaten Siak Tahun 2011-2013) - Hendra, Nofriko; Anwar, Khairul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research was conducted by Nofriko Hendra entitled Community's Participation in Rural Development Planning (Case Study in Jambai Makmur subdistrict Kandis Siak Regency Year 2011-2013), led by DR. Khairul Anwar, M.Sc.This study aims to look at how community participation in development planning in the village of Jambai Makmur subdistrict Kandis Siak, which in this study emphasized on community participation in the development planning process. In the process, it will be known how the form, manner, and the actors involved. However, in the planning process, the public is less involved in every stage of the planning process, in the sense that every process is always dominated by the village government.This research uses descriptive qualitative method. The theory used is the theory of the basic steps in any planning process by linking the community participation by Chambers and Taylor. Primary data and secondary data obtained from interviews with informants and observations on the object of research.From these results, it is known that public participation can be increased by growing awareness within the community about the importance of community participation in delivering the aspirations of the rural development planning process. Then the actors involved in the process most of the village government, while people over to the representatives of the region such as hamlets and RT / RW.Keywords: Public Participation, Planning, Rural Development